(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
This scientific article explores the intricate process of forming and the successive stages of development of stable word combinations within the context of linguistic studies. The analysis delves into the dynamic interplay between individual words that culminate in the emergence of cohesive and stable lexical units. Understanding the formation and evolution of such combinations is pivotal in unravelling the complexities of language structure and usage.